Untargeted metabolomics identifies the potential role of monocarboxylate transporter 6 (MCT6/SLC16A5) in lipid and amino acid metabolism pathways - Tianjing Ren; Robert S. Jones; Marilyn E. Morris (Wiley, 2022)
Abstract Monocarboxylate transporter 6 (MCT6; SLC16A5) is an orphan transporter protein with expression in multiple tissues. The endogenous function of MCT6 related to human health and disease remains unknown. Our previous transcriptomic and proteomic analyses in Mct6 knockout (KO) mice suggested that MCT6 may play a role in lipid and glucose homeostasis, but additional evidence is required. Thus, the objective of this study was to further explore the impact of MCT6 on metabolic function using untargeted metabolomic analysis in Mct6 KO mice. The plasma from male and female mice and livers from male mice were submitted for global metabolomics analysis to assess the relative changes in endogenous small molecules across the liver and systemic circulation associated with absence of Mct6. More than 782 compounds were detected with 101 and 51 metabolites significantly changed in plasma of male and female mice, respectively, and 100 metabolites significantly changed in the livers of male mice (p < .05). Significant perturbations in lipid metabolism were annotated in the plasma and liver metabolome, with additional alterations in the amino acid metabolism pathway in plasma samples from male and female mice. Elevated lipid diacylglycerol and altered fatty acid metabolite concentrations were found in liver and plasma samples of male Mct6 KO mice. Significant reduction of N‐terminal acetylated amino acids was found in plasma samples of male and female Mct6 KO mice. In summary, the present study confirmed the significant role of MCT6 in lipid and amino acid homeostasis, suggesting its contribution in metabolic diseases.